PENGARUH PEMBERIAN PAKAN DENGAN KADAR PROTEIN BERBEDA TERHADAP PERTUMBUHAN IKAN KAKAP PUTIH (Lates calcarifer) YANG DIPELIHARA DI BAK TERKONTROL - Della Febriana Putri; Limin Santoso; Suryadi Saputra (Fakultas Perikanan dan Kelautan, Universitas Riau, 2018)
This study aims to determine the optimal protein content in the feed for the growth rate of seabass (Lates calcarifer) through feeding with different protein levels maintained in the controlled tank. This study used a complete randomized design (RAL) with 46% protein content of commercial feed, 46% protein content of formulation and 48% protein content of formulation each treatment consisting of three replications. The results of this study as a whole of the parameters observed included absolute growth, daily growth rate, protein retention, and liveliness gave significantly different results between control treatment with P1 and P2, while for feed conversion ratio gave significantly different result between treatment control with P2, but not significantly different between controls with P1 and P1 with P2. .With the provision of seabass with different protein levels maintained in a controlled tank gives the best results in the control treatment with a 46% protein content.